(untitled) (LSP International Journal, 2018)
Due to the considerable volume of medical content knowledge that medical students have to acquire and memorise, very little time can be devoted to medical English learning. Therefore, an English language teacher has to find strategies to both motivate the learners and facilitate language acquisition inside and outside the classroom. Yet, very few teachers can claim to be experts in medical English. Most teachers are sent to university hospitals without prior training and are trained on the job, which is far from being satisfactory. Therefore, after illustrating the specificity of medical English as opposed to general English, this paper discusses the strategies that have been implemented in a medical faculty so as to optimize medical English classes. Finally, this paper will raise the issue of teacher training specifically in English for medical purposes and suggest some solutions to help teachers acquire the medical knowledge sufficient to design relevant and efficient course contents.